Multi-ligand simultaneous docking of Carica papaya leaf phytochemicals, Carpaine and Rutin reveal multi-mechanism inhibition of cancer proteins, BCL-2 and WWP1 - Merla Sudha; Asmita Saha; Belaguppa Manjunath Ashwin Desai; Anil Ranu Mhashal; Pronama Biswas (Phytomedicine Plus)
Cancer remains a major global health concern due to chemotherapy resistance and toxicity from high-dose treatments. To overcome these challenges, new therapeutic strategies targeting key proteins in cancer progression are essential. This study evaluates two phytochemicals, Carpaine (Car) and Rutin (Rut), from Carica papaya leaves, for their potential in enhancing cancer therapy by targeting B-cell lymphoma 2 (BCL-2) and WW domain-containing protein 1 (WWP1) proteins. We assessed their additive, allosteric, and synergistic effects using molecular docking, multi-ligand simultaneous docking (MLSD), molecular dynamics (MD) simulations, and MMPBSA analysis. Car and Rut showed an additive effect on BCL-2 by binding at distinct regions within the same pocket. MLSD revealed an improved binding affinity of -13.13 ± 0.08 kcal/mol, individual ligands or the commercial inhibitor Venetoclax. For WWP1, Car bound near the H-site and Rut near the Le-site, exhibiting an allosteric effect that increased Car’s binding affinity in MLSD to -15.59 ± 0.39 kcal/mol. Furthermore, Rut combined with bortezomib (Bortezomib) demonstrated a synergistic interaction with WWP1. Binding energies were -7.64 ± 0.156 kcal/mol for Bort, -10.26 ± 0.07 kcal/mol for Rut, and -15.59 ± 0.39 kcal/mol for MLSD, suggesting a more stable complex through synergy. These results suggest Car and Rut, particularly in combination with Bort, as promising candidates against cancer-related proteins BCL-2 and WWP1. Further experimental validation is warranted to explore their therapeutic potential.